Electrophoretically deposited L-cysteine functionalized MoS2@MWCNT nanocomposite platform: a smart approach toward highly sensitive and label-free detection of gentamicin. (December 2021) - Yadav, A.K.; Verma, D.; Solanki, P.R.
Abstract: The exploitation of antibiotics has caused many side effects on the agriculture, environment, and human health. The existing methods have numerous shortcomings in determining gentamicin (GEN), a broad-spectrum antibiotic that causes nephrotoxicity and ototoxicity when found in excess. Here, an immunosensing platform to detect GEN using multiwalled carbon nanotubes (MWCNTs) and molybdenum disulfide (MoS2 ) nanocomposite, deposited electrophoretically on indium tin oxide (ITO) glass has been developed. A novel 2-D graphene analog MoS2 @ MWCNTs nanocomposite was made via a facile and low-cost hydrothermal technique using l-cysteine to achieve remarkable electrochemical properties. Subsequently, a highly sensitive electrochemical immunosensor was fabricated by assembling monoclonal antibodies against gentamicin (anti-GEN) on a MoS2 @MWCNTs modified ITO electrode. The hetero-nanostructure formed on the immunosensor surface appeared relatively good conductor for accelerating the electron transfer. GEN was determined on anti-GEN modified electrodes by utilizing the differential pulse voltammetry technique by measuring the difference in current owing to the transfer of electrons directly between the redox species and immunoelectrodes. Under optimal experimental conditions, the fabricated immunosensor had a wide linear detection range of 1 × 10 −6 –40 μg/mL, a high sensitivity of 13.55 μA (log μg/mL) −1 and a low limit of detection and limit of quantification of 0.039 μg/mL and 0.130 μg/mL, respectively. The developed immunosensor also exhibits high reproducibility, repeatability, and good selectivity against various interferences. This electrochemical immunosensor having MoS2 modified MWCNTs displays the excellent potential for the point-of-care device for GEN testing. Highlights: Label-free, highly selective, and an ultrasensitive immunosensing platform for GEN detection. MoS2 @MWCNTs nanocomposite was synthesized using l-cysteine to achieve excellent electrochemical properties. l-Cysteine permits the positive charges on the nanocomposite to bind covalently with anti-GEN. Immunosensor had a wide linear detection range, high sensitivity and low LOD and LOQ. Successful detection of GEN in food samples showed excellent potential as POC device.